Leadership Styles and Power Bases Preferences of Primary School Administrators from the Perspective of Preservice Science Teachers - ŞAHİNGÖZ, Selçuk (Kastamonu Egitim Dergisi, 2022)
Purpose: The aim of this study is to examine the types of leadership that primary school administrators exhibit and the power bases they utilize from the perspective of preservice science teachers. Design/Methodology/Approach: Qualitative research design was applied in the study. The data were collected through the observations through 72 preservice science teachers during the Fall and Spring semesters and the assessment of the self-reports they prepared based on the semi-structured interviews with 18 school administrators. Findings: According to the obtained data from the preservice science teachers, leadership style preferences of school principals are more in favor of instructional and moral leadership styles. The result is similar for school vice principals, but shared leadership style is also added to the mentioned leadership styles. The findings also show that the school administrators use legitimate and expert power bases more than the other power bases in educational administration process. Highlights: The preservice science teachers additionally emphasized the school principals are greatly benefit from their charisma power on the contrary the school vice principals. On the other hand, they pointed out the school vice principals exhibit shared leadership more than the school principals. Last, the preservice teachers argued leadership preferences of the school administrators that aspect of science education related practices.
Keywords: Eğitim Üzerine Çalışmalar; Leadership styles; Power bases; Preservice science teachers; Primary education; School administrators; Studies on Education; 4. Education